Numerical study of seismic performance of grooved metallic-yielding damper made from shape memory alloys - Mingming Liu; Gaozhan Zhao; Kangning Liu (Journal of Engineering and Applied Science)
Abstract The utilization of novel engineering materials like shape memory alloys has significantly broadened their application scope within civil engineering. Consequently, this study examines the mechanical performance of a grooved metallic-yielding damper fabricated from shape memory alloys. The seismic performance of the new system has been studied using the nonlinear static analysis method in ABAQUS software. Also, after a parametric investigation, the applicability of this kind of damper in a steel frame has been evaluated using the nonlinear dynamic analysis and considering the accelerograms of near-fault and far-fault earthquakes. The superelastic behavior of shape memory alloys has been applied to ABAQUS software by using the Brinson model and considering phase transformations. Lastly, the effect of various geometric parameters on the steel frame’s seismic performance, including stiffness, ductility, and energy absorption capability, has been studied. The results indicate that the ductility of the presented new damper is 56 and is greater than ductility of many conventional metal damper. Also, studied damper has great energy absorption and can easily replace other metallic-yielding dampers including ADAS and TADAS. Moreover, it is evident that the proposed system exhibits substantially enhanced energy absorption and ductility equated to the braced frame equipped with the equivalent steel damper, thus rendering it suitable for engineering applications.